Post-Nominal Modifier in English Job Advertisements in Jobstreet.com - Krisna Yudha Bakhti (LPPM Universitas Bina Sarana Informatika, 2020)
The language features of job advertisements are in the form of simple sentences and complex nominal groups so that a job advertisement can cause different perceptions between one reader and another. Therefore, carefulness in understanding job advertisements is a matter of urgency. One characteristic of a complex nominal group is the use of a post-nominal modifier which functions to give a clear meaning to the nominal group itself. This study examines the use of post-nominal modifiers which aim to identify the constituent elements and types of circumstantial elements in post-nominal modifiers contained in English language job advertisements. The job advertisements were obtained from one of the largest job market websites in Indonesia, jobstreet.com. This study used descriptive qualitative method through the Systemic Functional Linguistics (SFL) approach. From this study, it was found that all post-nominal modifiers consisted of prepositional phrases with the preposition